PENGARUH ARUS KAS BEBAS DAN PROFITABILITAS PADA KEBIJAKAN UTANG PERUSAHAAN REAL ESTATE DI BURSA EFEK INDONESIA - Suastawan, I Putu (E-Jurnal Akuntansi; Vol 9 No 3 (2014), 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 This study aims to determine the effect of free cash flow and profitability of the real estate company's debt policy in Indonesia Stock Exchange. This research was conducted in a real estate company in Indonesia Stock Exchange (IDX). The number of samples taken 11 companies listed in Indonesia Stock Exchange. This study used purposive sampling method in particular judgment sampling. Based on the results of linear regression analysis showed that significant free cash flow of 0,800 partially illustrating that free cash flow does not significantly influence the company's debt policy. In addition, the profitability variable has a significance of 0.015, which means that the partial debt policy affect the profitability of real estate companies in IDX.